Effect of morningness-eveningness chronotype on academic performance of undergraduate students - Haider Imam; Deepika Singla; Ruchi Basista (Bulletin of Faculty of Physical Therapy, 2024)
Abstract Background Circadian rhythms are crucial for physiological functioning, and they vary among people. There are three distinct chronotypes: morning, evening, and neither type. Morning types experience their highest level of activation during the early part of the day and tend to be more conscientious and focused on achieving their goals. Evening types, on the other hand, reach their peak performance during the latter portion of the day and exhibit a higher level of intelligence. University class schedules may occasionally clash with evening-type individuals’ circadian preferences, potentially impacting their academic performance in comparison to their morning-type peers. Therefore, this study was done to investigate if morningness-eveningness can affect college students’ academic performance as sleeping late or sleep deprivation can lead to disease in the young population. Materials and methods A sample of 100 collegiate students aged 18–30 years were recruited via convenience sampling from Jamia Hamdard, Delhi, and informed consent was obtained from the subjects. The morningness-eveningness questionnaire (MEQ) was used to assess students’ chronotype, and the mean of the last three academic years percentage was used to assess the academic performance of the students. Results The total academic performance score was better in the morning category (75.53 ± 7.28) as compared to the evening (66.42 ± 10.08) and intermediate (73.72 ± 6.46) categories. There was a low degree of positive correlation between total academic performance and TMEQ (total morning-evening questionnaire) score (ρ = 0.204). Conclusion The academic performance of morning chronotype students was better than that of evening chronotype students.